Formulating, packaging, and marketing of natural cosmetic products - Dayan, Nava.; Kromidas, Lambros; Wiley InterScience (Online service) (Hoboken, N.J. : Wiley, 2011)
Balanced coverage of natural cosmetics, and what it really means to be "green" The use of natural ingredients and functional botanical compounds in cosmetic products is on the rise. According to industry estimates, sales of natural personal care products have exceeded $7 billion in recent years. Nonetheless, many misconceptions about natural products-for instance, what "green" and "organic" really mean-continue to exist within the industry. Formulating, Packaging, and Marketing of Natural Cosmetic Products addresses this confusion head-on, exploring and detailing the sources, processing, safety, efficacy, stability, and formulation aspects of natural compounds in cosmetic and personal care products. Designed to provide industry professionals and natural product development experts with the essential perspective and market information needed to develop truly "green" cosmetics, the book covers timely issues like biodegradable packaging and the potential microbial risks they present, the use of Nuclear Magnetic Resonance (NMR) to identify biomarkers, and chromatographic methods of analyzing natural products. A must-read for industry insiders, Formulating, Packaging, and Marketing of Natural Cosmetic Products provides the reader with basic tools and concepts to develop naturally derived formulas.
Frontmatter -- Color Plates -- Market and Trends. The Natural Personal Care Market / Darrin C Duber-Smith -- Consumer and Formulator of Natural Cosmetics: Understanding and Integrating Each Other's Needs / Yi Hsin Chang -- The Mechanics of Developing a Natural/Organic Nongovernmental Cosmetic Standard / Amy B Olson -- Regulatory Aspects. Regulatory Perspective of Natural and Organic Cosmetic Products / Azalea P Rosholt -- The U.S. Legal Perspective on Making Organic and Natural Claims for Cosmetic Products / Miriam J Guggenheim, Maryjoy Ballantyne -- Regulatory and Safety Aspects of Natural Fragrance Ingredients / Anne Marie Api, Matthias Vey -- Advertising Self-Regulation: A Review of Cosmetic Claims and Natural/Organic Claims / Annie M Ugurlayan -- Safety Aspects. The Safety Assessment of Plant-Derived Ingredients in Cosmetics / Viny Srinivasan, Eric Antignac -- Approach to Assessing Consumer Safety of Botanical Ingredients with Emphasis to Type I Allergy / Esperanza Troyano, Donna McMillan, Katherine Sarlo, Lijuan Li, Rohan Wimalasena -- Preserving Cosmetics with Natural Preservatives and Preserving Natural Cosmetics / James Flanagan -- Microbial Risks and Eco-Friendly Packaging / John I Yablonski, Sharon E Mancuso -- Use of Natural Ingredients. Formulating Cosmetics with Natural Oils, Fats, Butters, and Waxes / Mark Garrison, Nava Dayan -- Natural Antioxidants and their Effects on the Skin / Anne Pouillot, Luigi L Polla, Philippe Tacchini, Alice Neequaye, Ada Polla, Barbara Polla -- The Use of Quercetin and Curcumin in Skin Care Consumer Products / Brian E Kilfoyle, Diksha Kaushik, Jenna L Terebetski, Sonali Bose, Bozena B Michniak-Kohn -- Ayurvedic Ingredients in Cosmetics / Rajarajeswari Sivalenka, Mangathayaru Putrevu -- Formulating with Traditional Chinese Medicine Herbs / Ina Schlenoff, Robin Choi -- The Inside-Out Concept as Complement to the Use of Topical Sunscreen: The Case for Endogenous Skin Photoprotection from Sunlight by Natural Dietary Actives such as Tomato Carotenoids / Joseph Levy, Yoav Sharoni -- Analysis of Naturals. Chromatographic Techniques for the Analysis of Natural Products in Cosmetics / Stefan Gafner, Jacquelyn R Villinski -- The Use of Nuclear Magnetic Resonance Spectroscopy for the Identification of Biomarkers for Quality Control of Plant Extracts / Kan He, Marc Roller -- Biodegradation. Biodegradability Evaluation for Cosmetic Ingredients and Finished Products / Jennifer K Saxe -- Overview of Biodegradable Packaging, Methods, and Current Trends / Gaurav Kale -- Index.
Print version record.
Keywords: Cosmetics -- Composition; Cosmetics containers; Organic compounds; Cosmetics -- Composition; Cosmetics containers; Organic compounds; Electronic books; Electronic resource